Potential of Zakat on MSME Growth in Indonesia's Economic Recovery - Ario Hernest Hadinata; Irham Zaki (AFEBI Islamic Finance and Economic Review, 2020)
This article explains how the potential of zakat, where Indonesia is the country with the largest Muslim population in the world. Certainly with the largest Muslim population. Indonesia has great zakat potential. Based on the research of Baznas, Bogor Agricultural University (IPB), and Islamic Development Bank (IDB), the potential of national zakat amounted to Rp 217 trillion. So in this case it takes planning how the program of distribution of zakat can be channeled in a directed manner and has a clear orientation where zakat will be distributed, not just on the distribution of a moment without any sustainable effect. The author has an idea about the system of distribution of zakat that can be channeled to MSMEs with a revenue-sharing system so that the zakat can later be re-collected and used for further purposes. In the end, the orientation of the idea of zakat distribution program to MSMEs can have a sustainable impact. Then on the next side poverty can be resolved, unemployment can be realized, and welfare can be felt by all communities so that the expected benefits in the Islamic economy can be realized.